Conceptual foundations of G. V. Plekhanov and N. A. Berdyaev - Kulak, Nikita I. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article aims to analyse how the formation of the philosophical credo of N. A. Berdyaev and his formation in the role of criticism of Marxist philosophy in the context of the materialistic research of G. V. Plekhanov. It is shown that the views of G. V. Plekhanov on the critical processing of the principles of the materialist understanding of history are a reaction to the philosophical system of N. A. Berdyaev. In turn the degree of influence of Russian philosophical systems on the views of N. A. Berdyaev, which implicitly made it possible to correct the historical and philosophical concept of G. V. Plekhanov. The hypothesis of four factors is substantiated, such as the importance of the family of N. A. Berdyaev and personally the elder brother S. A. Berdyaev, the philosophical atmosphere of the beginning of 21th century, in Europe, the degree of influence on the formation of his methodological credo P. B. Struve and attitude to the work of G. V. Plekhanov, who made it possible to clarify and substantiate in more detail the contradictory premises of their historical and philosophical concepts. The work uses the method of comparative studies to describe the categorical apparatus of thinkers.
Keywords: G. V. Plekhanov; N. A. Berdyaev; P. B. Struve; materialist understanding of history; Russian Marxism philosophy